Deposition, Clearance, and Reinduction of Amyloid A Amyloid in Interleukin 1 Receptor Antagonist Knockout Mice. (January 2017) - Watanabe, K.; Uchida, K.; Chambers, J. K.; Ushio, N.; Nakayama, H.
Amyloid A (AA) amyloidosis is characterized by the extracellular deposition of AA amyloid and results in the irreversible dysfunction of parenchymal organs. In experimental models, AA amyloid deposits are cleared following a decrease in circulating serum amyloid A (SAA) concentrations. Additional inflammatory stimuli during this recovery process may induce more severe amyloid redeposition. In the present study, we confirmed the deposition, clearance, and reinduction of AA amyloid deposits in interleukin 1 receptor antagonist knockout mice (IL-1raKO) and studied the SAA levels and amyloid-enhancing factor activity based on the time-dependent changes of amyloid deposition. Histopathologically, following initial (day 0) injection of amyloid-enhancing factor in combination with an inflammatory stimulus (silver nitrate [AgNO3 ]), amyloid deposition peaked by day 20, and its deposition gradually decreased after day 35. SAA concentrations in serum were precipitously elevated on day 1 but returned to normal levels by day 10, whereas the SAA dimer was detected in serum after day 45. An additional AgNO3 injection was administered to mice with amyloidosis on day 5, 10, 35, or 50, and all mice developed large amyloid deposits. Amyloid deposition was most severe in mice treated with AgNO3 on day 35. The inoculation of sera from mice with AA amyloidosis, combined with AgNO3, induced AA amyloidosis. Serum samples collected on days 35 and 50, which contained high concentrations of the SAA dimer, induced amyloidosis in a high proportion (83%) of mice. Therefore, increased SAA and/or its dimer in serum during the recovery process may markedly exacerbate the development of AA amyloidosis.